Evaluation of staging, cytoreduction and second-look operation of 119 ovarian cancer patients - Murta, Eddie Fernando Candido (1997)
OBJECTIVE:This study was conducted on patients with ovarian cancer in order to evaluate survival. DESIGN: A retrospective study of 119 cases of ovarian cancer from January 1977 to December 1992 with observation until 1993. LOCATION: Department of Gynecology and Obstetrics, Ribeirão Preto School of Medicine, São Paulo University. PARTICIPANTS: Of the 119 cases, 70 (58.8%) presented epithelial carcinomas and 21 (17.6%) tumors of the sexual girdle/stroma. DATA SOURCE: The data were obtained from the medical records of the patients. MEASUREMENT: Statistical analysis of survival time was based on the nonparametric Mann-Whitney test with the level of significance set at P < 0.05. RESULTS: The patients with a negative second look had a mean survival of 79.4 ± 48.5 months versus 24.2 ± 15.1 months for patients with a positive second look (P < 0.02). CONCLUSIONS: It is concluded that patients with a negative second look present a better prognosis compared to those with residual disease.